Copper sulfide-functionalized molybdenum disulfide nanohybrids as nanoenzyme mimics for electrochemical immunoassay of myoglobin in cardiovascular disease. Issue 5 (12th January 2017) - Zhang, Bo; Zhang, Yi; Liang, Wenbin; Yu, Xuejun; Tan, Hu; Wang, Guoqiang; Li, Aimin; Jin, Jun; Huang, Lan
Abstract : Myoglobin is one of the most commonly used cardiac biomarkers for the clinical diagnosis of acute myocardial infarction, which is the leading cause of mortality worldwide. Abstract : Myoglobin is one of the most commonly used cardiac biomarkers for the clinical diagnosis of acute myocardial infarction, which is the leading cause of mortality worldwide. Herein, we report a novel 'signal-on' electrochemical immunosensing system for the quantitative detection of myoglobin without the need for natural enzymes and additional electron mediators. The assay was readily carried out on a monoclonal mouse anti-human myoglobin capture antibody-modified carbon fiber microelectrode using copper sulfide–molybdenum disulfide (CuS–MoS2 ) hybrid nanostructures conjugated with polyclonal rabbit anti-human myoglobin detection antibody. Upon introduction of target myoglobin into the detection system, sandwiched immunocomplexes were formed on the electrode between the capture antibody and the detection antibody accompanying the CuS–MoS2 nanohybrids. The carried CuS–MoS2 nanohybrids acted as nanoenzyme mimics to electrochemically oxidize the glucose substrate, thereby resulting in the increment of the anodic current. Under optimal conditions, the detectable currents exhibited a 'signal-on' response relative to myoglobin concentrations within a dynamic linear range of 0.005–20 ng mL −1, with a limit of detection (LOD) as low as 1.2 pg mL −1 . In addition, the electrochemical immunosensing platform displayed high specificity, good precision and reproducibility, and acceptable method accuracy for determining human serum specimens from cardiovascular disease patients with consistent results obtained from the referenced enzyme-linked immunosorbent assay (ELISA) method.